Sustainability Beyond Compliance: Exploring Technology`s Role in Driving Sustainability Across Supply Chains - Peesapati, Sri Rama Yashaswi (International Journal of Supply Chain Management, 2024)
This paper discusses the growing importance of adopting sustainability in supply chains beyond compliance. This paper is based on a comprehensive examination of over 30 literary works to provide a thorough analysis of the subject matter. The study sheds light on the imperative of sustainability in supply chains considering environmental, social, and business efficiency aspects, as well as the influence of conscious consumers and investors. The objective of this paper is to delve into how emerging technologies can be utilized to solve the challenges in adopting Sustainability in Supply Chains. The discussion focuses on sustainability beyond compliance, and the role of technology. The findings highlight that the emerging digital technologies such as big data analytics, the Internet of Things (IoT), Block chain technology Artificial Intelligence (AI) offer promising avenues for companies to achieve sustainability in supply chains.